EMPLOYMENT ABSORPTION CONDITIONS IN THE CAPITAL CITY OF NUSANTARA: AN ANALYTICAL - Kustiawan, Andriawan; Sukarso, Aso; Hanapia, Asep Yusup; Purwinahyu, Purwinahyu; Darma, Dio Caisar; Nugraha, Cindera Syaiful; Ashari, Ihsan (Eksis: Jurnal Riset Ekonomi dan Bisnis, 2026)
There have been few studies examining the link between open economic and demographic policies and the integration of socio-economic indicators into employment, particularly in developing markets. To address this gap in the literature, this scientific paper investigates the relationship between foreign investment capital and population growth on labor force participation, considering the mediating roles of minimum wages, economic growth, and human development. The study focuses on the Capital City of Nusantara (IKN) as a representation of a new economic growth center in Indonesia. Time-series secondary data from official government sources covering the period 2011–2024 were calculated using moderated regression analysis (MRA). The empirical results reveal that foreign investment capital has a significant negative effect on minimum wages, while population growth significantly and positively influences regional economic growth. Statistically, foreign investment capital significantly reduces human development. Moreover, foreign investment capital, when moderated by minimum wages and regional economic growth, as well as population growth moderated by human development, exerts a significant positive impact on labor force participation. These findings suggest that additional macroeconomic components beyond the current model warrant the attention of policymakers and further research.